2021
DOI: 10.1042/bsr20210021
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of the abnormal lncRNA–miRNA–mRNA network in hypoxic pulmonary hypertension

Abstract: The incidence of hypoxic pulmonary hypertension (HPH) is increasing. Accumulating evidence suggests that long non-coding RNAs (lncRNAs) play an important role in HPH, but the functions and mechanism have yet to be fully elucidated. In this study, we established an HPH rat model with 8 h of hypoxia exposure (10% O2) per day for 21 days. High-throughput sequencing identified 60 differently expressed (DE) lncRNAs, 20 DE miRNAs and 695 DE mRNAs in rat lung tissue. qRT-PCR verified the accuracy of the results. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Additionally, KEGG analysis indicated that PI3K-Akt signaling pathway was significantly enriched, which was consistent with the previous demonstration that hypoxia response involves crosstalk with proliferation and apoptosis mechanisms [20,21]. And research conducted by Liu et al demonstrated that the immune response, inflammatory response, cellular response to interleukins, cell cycle, and leukocyte migration were highly enriched, suggesting that immune and inflammatory response pathways participate in HPH [22], which was partially consistent with the hypoxia-related inflammatory response enriched in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, KEGG analysis indicated that PI3K-Akt signaling pathway was significantly enriched, which was consistent with the previous demonstration that hypoxia response involves crosstalk with proliferation and apoptosis mechanisms [20,21]. And research conducted by Liu et al demonstrated that the immune response, inflammatory response, cellular response to interleukins, cell cycle, and leukocyte migration were highly enriched, suggesting that immune and inflammatory response pathways participate in HPH [22], which was partially consistent with the hypoxia-related inflammatory response enriched in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Shuang-Lan Xu et al [28] and Jie Liu et al [29] identi ed the differentially expressed circRNA/miRNA/mRNA and lncRNA/miRNA/mRNA in rat HPH model compared with controls, respectively. Their target genes were enriched in immune and in ammation-related pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies increasingly support the idea that lncRNAs play a role in influencing dysfunction in pulmonary arterial endothelial cells (PAECs) and the remodeling of pulmonary vasculature through various pathways [ [44] , [45] , [46] ]. According to the ceRNA hypothesis, the regulatory mechanism involves lncRNAs acting as competitive endogenous RNAs (ceRNAs), influencing gene expression in pulmonary hypertension (PH) through the competition for shared microRNAs (miRNAs) [ 47 , 48 ]. The m6A regulator were involved in the modification of noncoding RNAs [ 49 ].…”
Section: Discussionmentioning
confidence: 99%